Risky feet in patients with diabetes mellitus type 2 in the Primary Health Care during 2016 - Dania Lilia Cardona Garbey; Lissette Vinent Despaigne; Julio Cesar Cala Cardona; Elio Zaldivar Álvarez; Armando Rodríguez Salvá (Centro Provincial de Información de Ciencias Médicas, 2018)
An observational, descriptive and cross-sectional study to determine the stratification of the risky feet and the concurrent factors in 534 patients with diabetes mellitus type  2, belonging to the health areas of  "Dr. Carlos J. Finlay" and "Julián Grimau" Teaching polyclinics in Santiago de Cuba municipality was carried out during the second trimester of 2016 and they were classified in their corresponding doctors´ offices. Among the main results there were the increased frequency in the 1, 2 and 3 degrees of the stratification of the risky foot and the low frequency in the category without risk, while among the concurrent factors the plantar hyperkeratosis, the hallux valgus, more than 40 years of age, peripheral neuropathy, the peripheral arterial disease, inadequate shoes and obesity prevailed.